GIVE EDUCATION TO THE JAVANESE PEOPLE!’: KARTINI’S ASPIRATIONS FOR EDUCATIONAL EQUALITY IN THE 1903 NOTE - Deya Sofia; Muzakki Bashori (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines colonial education in the Dutch East Indies within the framework of the Ethical Policy and analyzes Kartini’s aspirations for educational equality through her 1903 memorandum, “Educate the Javanese!”. Unlike studies that primarily focus on Kartini’s personal correspondence, this research examines the memorandum as a formal policy proposal addressed to the colonial government. Using the historical method and library research, the study analyzes the 1903 memorandum, Kartini’s correspondence, and relevant historiography. The findings show that Kartini viewed the limited educational development of the Javanese people as a consequence of restrictive colonial policies. To address this condition, she proposed educational reforms that included character-oriented education for the indigenous aristocracy, women’s education as the foundation of social progress, expanded access to literacy, and the development of professional competencies. These ideas reflect Kartini’s vision of education as a strategic instrument for social transformation and the realization of educational equality.